The Elements of Lust and Affection in the Love Pantuns of Brunei Malays in Sabah - On, Low Kok (Malay Literature, 2016)
The Brunei Malay ethnic group settled all along the western shores of Sabah since the early part of the formation of the Brunei Malay Sultanate. As is the case with other Malay ethnic groups in Nusantara, reciting the pantun is part of their unique culture since the bygone days until the present time. In a field study conducted in several Malay Brunei kampongs along the western shores of Sabah, a number of pantuns with the themes of love and affection were recorded, transcribed and documented. These love pantuns that have been collected , among other things highlight the elements of yearning, falling in love, feeling amorous and wanting to seek a person's hand in marriage. Apart from documenting some pantuns with the themes of love and affection, the focus of this article is on the element of lust which is reflected in these pantuns of love of the Brunei Malays. In addition, a comparison will be made between these love pantuns and selected Malay and Straits-born Chinese pantuns. By making this analysis, the uniqueness of the elements of lust and affection in Brunei Malay pantuns will be unravelled. Keywords: Brunei Malay, loved pantun, affection, elements of lust